Julien Gracq's great freedom - Vicente, Adalberto Luis (ITINERÁRIOS – Revue de Littérature, 2010)
Julien Gracq is one of the foremost French novelists of the twentieth century. In 1945, his single anthology of prose poems, Liberté Grande, is published. The high poetic voltage of the texts gathered in the anthology distances itself from the controlled lyricism of the author’s novelistic prose. Infl uenced by Rimbaud’s poetry and by Surrealism, Gracq’s prose poems state the primacy of creative imagination over the impositions and limitations of reality, as can be seen from the reading of the fi rst poem in the anthology, “Pour galvaniser l’urbanisme”, which is the focus of this paper.